Enhancement Quality Learning Student in implementing Project Strengthening Profile Pancasila Students (5P) with Lifestyle Theme Continuing at Karya Pembangunan Baleendah High School - Iis Suryani; Cucu Suwandana; Amir Supriatna; Sidiq Aulia Rahman; Kustasi Kustasi; Sobari Sobari; Kustati Waska Warta; Supyan Sauri (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
In the context of post-pandemic recovery of learning from Covid 19, the Ministry of Education and Culture 2022 will roll out the Independent Curriculum Implementation (IKM) program for the Independent pathway category which consists of 3 categories, namely Independent Learning IKM, Changing Independent IKM, and Independent Sharing IKM. Karya Pembangunan (KP) Baleendah High School is a school implementing the Independent Changing IKM category which must implement the Independent Curriculum in the 2022/2023 academic year for class X students, using teaching tools from the government or adapt them according to the conditions of Baleendah KP High School, as well as implementing the Cocurricular Strengthening Project Pancasila Student Profile (5P). In realizing the Pancasila student profile which acts as the main reference that directs educational policies including being a reference for educators in building the character and competence of students, the implementation is carried out through intracurricular, co-curricular activities (5P project), extracurriculars and school culture/climate. The form of community service carried out at KP Baleendah High School is a form of training in carrying out co-curricular activities of the Pancasila Student Profile Strengthening Project (5P) with the theme